P0570THE INCIDENCE, RISK FACTORS OF ACUTE KIDNEY DISEASES AND DISORDERS AND ITS IMPACT ON CHRONIC KIDNEY DISEASE IN PATIENTS AFTER RADICAL CYSTECTOMY. (6th June 2020) - Ge, Shengnan; Tang, Ying; Chen, Junzhe; Yu, Wenjuan; Xu, Anping
Abstract: Background and Aims: Acute kidney injury (AKI) is a widely-discussed complication associated with the radical cystectomy which is the gold standard for the management of invasive bladder cancer. Until now, few studies investigate the new criteria named Acute Kidney Diseases and Disorders(AKD) as the complication of radical cystectomy. In this study, we evaluated the incidence, risk factors of AKD and evaluate its impact on chronic kidney disease (CKD) in patients after radical cystectomy. Method: A total of 279 patients who underwent radical cystectomy at Sun Yat-sen Memorial Hospital, Guangzhou, China, from January 2006 to June 2019 were evaluated, including 168 patients for Robotic-assisted Laparoscopic Radical Cystectomy (RLRC) and 111 patients for Laparoscopic Radical Cystectomy(LRC). AKD was diagnosed according to the classification scheme proposed in the 2012 KDIGO guideline. Logistic regression modeling was used to explore risk factors of AKD, while risk factors associated with CKD in AKD patients were investigated using Kaplan-Meier analysis, respectively. Results: The overall incidence of AKD after radical cystectomy was 34.1% (95 out of 279), the incidences differ significantly between the RLRC and LRC groups (67 [39.9%] vs 28 [25.2%], P =0.011). Among 279 patients, risk factors associated with postoperative AKD included RLRC (OR 2.067, 95%CI 1.188 to 3.595, P=0.010), Age (years) (OR 1.046, 95%CI 1.018 to 1.074, P =0.001), baseline eGFR<60(ml/(min.1.73m 2 ) (OR 2.662, 95%CI 1.355 to 5.230, P =0.004), Further subgroup analysis identified age, operation time<250(min) as important risk factors of AKD in RLRC patients but not in LRC patients. Of 211 patients with a preoperative estimated glomerular filtration rate (eGFR) of > 60 ml/min/1.73 m2, CKD developed in 16.0% (21/ 131) of patients in the non-AKD group and 36.3% (29/ 80) of patients in the AKD group. Kaplan-Meier analysis(shown in figure 1) identified that AKD is associated with higher CKD rates in those patients ( P <0.001). Conclusion: One-third of bladder cancer patients developed AKD after after radical cystectomy. RLRC, Age, baseline eGFR <60(ml/(min.1.73m 2 ) were independent risk factors for postoperative AKD in all patients. Occurance of AKD could increase the risk of new-onset CKD in the long run. Though the use of RLRC is now well established, we should be aware that it may increase the risk of postoperative AKD, especially for patients who are old and with lower eGFR .Besides, we should try to improve the management of those AKD patients with aim toward preventing further development of CKD.